2020
DOI: 10.1071/en19115
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography-tandem mass spectrometry as a fast and simple method for the determination of several antibiotics in different aqueous matrices

Abstract: Environmental contextAntibiotic residues released to the environment could influence the selection of antibiotic-resistant bacteria and hence their spread within the aquatic environment. We report a multi-method approach for determining 47 antibiotics in wastewater, surface water, drinking water and groundwater. The method provides a rapid screening of water samples for common antibiotics that have the potential to alter natural bacterial populations. AbstractA simple and rapid liquid chromatography-electrospr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Due to the large number of substances to be analyzed, a method was developed for simultaneous analysis of 64 illicit compounds using a scheduled multiple reaction monitoring (s-MRM) algorithm monitor. The s-MRM improved the quality of the chromatograms, signal response, and enhanced signal to noise (S/N) ratio, resulting in more data points [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the large number of substances to be analyzed, a method was developed for simultaneous analysis of 64 illicit compounds using a scheduled multiple reaction monitoring (s-MRM) algorithm monitor. The s-MRM improved the quality of the chromatograms, signal response, and enhanced signal to noise (S/N) ratio, resulting in more data points [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study also revealed that the SXT resistance was predominant (52.1%) among the K. pneumoniae strains, one-third of which were also resistant to CHL (31.9%) and TET (27.7%). SXT belonged to the fluoroquinolone antibiotics and was frequently detected in surface water environments [ 62 ]. A high occurrence (28%) of SXT-resistant K. pneumoniae strains was also found in untreated hospital waste in Bangladesh [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic concentrations of ciprofloxacin, meropenem, and piperacillin were determined as previously described (Voigt et al . 2020a; Voigt et al . 2020b).…”
Section: Methodsmentioning
confidence: 99%